Ubiquitin C-terminal hydrolase-L1 as a biomarker for ischemic and traumatic brain injury in rats - Liu, Ming C.; Akinyi, Linnet; Scharf, Dancia; Mo, Jixiang; Larner, Stephen F.; Muller, Uwe; Oli, Monika W.; Zheng, Wenrong; Kobeissy, Firas; Papa, Linda; Lu, Xi-Chun; Dave, Jitendra R.; et al. (The European journal of neuroscience, 2010)
Ubiquitin C‐terminal hydrolase‐L1 (UCH‐L1), also called neuronal‐specific protein gene product 9.5, is a highly abundant protein in the neuronal cell body and has been identified as a possible biomarker on the basis of a recent proteomic study. In this study, we examined whether UCH‐L1 was significantly elevated in cerebrospinal fluid (CSF) following controlled cortical impact (CCI) and middle cerebral artery occlusion (MCAO; model of ischemic stroke) in rats. Quantitative immunoblots of rat CSF revealed a dramatic elevation of UCH‐L1 protein 48 h after severe CCI and as early as 6 h after mild (30 min) and severe (2 h) MCAO. A sandwich enzyme‐linked immunosorbent assay constructed to measure UCH‐L1 sensitively and quantitatively showed that CSF UCH‐L1 levels were significantly elevated as early as 2 h and up to 48 h after CCI. Similarly, UCH‐L1 levels were also significantly elevated in CSF from 6 to 72 h after 30 min of MCAO and from 6 to 120 h after 2 h of MCAO. These data are comparable to the profile of the calpain‐produced αII‐spectrin breakdown product of 145 kDa biomarker. Importantly, serum UCH‐L1 biomarker levels were also significantly elevated after CCI. Similarly, serum UCH‐L1 levels in the 2‐h MCAO group were significantly higher than those in the 30‐min group. Taken together, these data from two rat models of acute brain injury strongly suggest that UCH‐L1 is a candidate brain injury biomarker detectable in biofluid compartments (CSF and serum).